Status of Primary School Specialty Education - case study of Shantou City - Jiang, Zihao; Bi, Chuanchen (Technium Social Sciences Journal, 2023)
This study takes Shantou City's primary education occupational labor force demand as a starting point，which determines the relevant concepts of vocational education for primary school teachers. By the means of literature analysis, investigation as well as interview methods, this paper investigated the training status and employment status of various majors in primary education, mathematics education, and primary education (general subjects) in Shantou Vocational and Technical College. First, the current situation of the school's current vocational education training is analyzed in terms of the existing professional training plans of each major in recent years. Second section is about the interviews and surveys on the current situation of the above-mentioned students of each major. The survey will be based on the students' personal information, students' acceptance of training, employment tendency, existing employment opportunities, long-term career and other pain points. The last section is about the investigation the needs of employers for primary school teachers in recent years.